1992
DOI: 10.1136/gut.33.7.922
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of ulcerative colitis with fish oil supplementation: a prospective 12 month randomised controlled trial.

Abstract: The effect offish oil on the course ofulcerative colitis was investigated in a randomised blinded controlied study. Eighty seven patients received supplements of 20 ml HiEPA fish oil as triglyceride (4.5 g of eicosapentaenoic acid) or olive oil placebo daily for one year. The oils were given in addition to standard drug therapy and trial entry was stratified for disease activity. Fish oil significantly increased the eicosapentaenoic acid content of rectal mucosa to 3.2% of total fatty acids at six months, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
0
4

Year Published

1993
1993
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(139 citation statements)
references
References 27 publications
5
130
0
4
Order By: Relevance
“…observed that the levels of unsaturated fatty acids, EPA and DHA increased in rectal mucosa after ω-3 PUFA supplementation (34). A similar effect on colonic fatty acid profile was seen by…”
Section: Discussionsupporting
confidence: 64%
“…observed that the levels of unsaturated fatty acids, EPA and DHA increased in rectal mucosa after ω-3 PUFA supplementation (34). A similar effect on colonic fatty acid profile was seen by…”
Section: Discussionsupporting
confidence: 64%
“…The first trial, which was an open study, showed no benefit whereas the latter two studies, which were larger, better controlled and used higher doses, showed mild to moderate symptomatic improvement. Hawthorne et al (1992) reported mild clinical benefit and decreased requirement for corticosteroids in a double-blind controlled trial of fish oil in colitis.…”
Section: T a B Sanders Influences Of N-3 Fatty Acids On The Immumentioning
confidence: 99%
“…Consistent with this, the low incidence of IBD among the Inuit has been attributed to their habitual high intake of n-3 fatty acids, particularly eicosapentaenoic acid (20:5n-3) and docosahexaenoic acid (22:6n-3) from marine foods (6). High dietary intakes of n-3 fatty acids have also shown therapeutic benefit in experimental models of colitis (1,36,37,49) and in several clinical studies including patients with ulcerative colitis and Crohn's disease (4,7,18,45). The absence of significant therapeutic efficacy in some clinical trials of n-3 fatty acids in patients with IBD (31,33) may be explained by differences in study design, patient selection, and the formulation, dose, and duration of n-3 fatty acids (6).…”
mentioning
confidence: 99%